What can ANS signals tell us about motor learning? An implication for better assessment of cognitive contribution to motor learning - Yokoi, Atsushi (Frontiers in Behavioral Neuroscience, 2025)
Motor learning is supported by both explicit and implicit processes. A central question in the field of motor control is how these two processes interact and, critically, how each process can be assessed in an unbiased manner. In this perspective paper, we propose that the autonomic nervous system (ANS) offers an informative window into explicit cognitive processes during motor learning. We first briefly review studies outside the motor learning domain, where ANS activity has been linked to internal cognitive states such as surprise and uncertainty. We then discuss how these ANS-related states can be leveraged to assess the manifestation and influence of explicit processes during motor learning, as well as to explore cognitive computations that may involve central ANS activity, including contextual inference.